Men’s Attachment to Masculinity and Preference in Accessing Primary Health Care Service in URBAN Area of Surabaya, Indonesia - Setho Hadisuyatmana (Journal of Global Pharma Technology, 2020)
Men’s attachment to masculinity is believed to contribute to the low access to health services. However, there is a paucity in the available literature to explain this further in Indonesia. This study aimed to narrow the gap by providing scientific evidence to explain whether a similar situation is occurring in Indonesia. We conducted a cross-sectional study involving 134 men aged 20-40 years old who lived in Surabaya as participants. The ideology of masculinity, masculinity norms and the gender role conflict were assessed for their correlations with men’s access to primary health care. Univariate analysis was employed to identify the studied variables; and bivariate analysis was conducted to the correlation with men’s use of the primary health care services, using Spearman’s correlation test. The men were moderately attached to the ideology of masculinity (52.2%), masculinity norms (56.7%) and have moderate gender role conflicts (53.7%), and used the primary health care center for services (54.5%). The bivariate analysis resulted that all the three studied variables did not correlate with men’s access to primary health care centers (p = 0.455, 0.654, 0.300 respectively). The results refute the widely accepted notion and suggest that the men’s attachment to masculinity did not contribute to their use of primary health care service. Instead, the men would access the primary health service as early as physical symptoms started to occur.Keywords: Health service utilization, Indonesia, Masculinity, Men, Primary health care.